KONSEP KEPEMIMPINAN PEREMPUAN DALAM LEMBAGA PENDIDIKAN ISLAM - Dennis Haruna; Novita, Lenny; Yusrawati, Yusrawati; Junaidi, Junaidi (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2025)
This study aims to comprehensively examine the concept of women's leadership in Islamic educational institutions from normative (Al-Qur'an and Hadith) and empirical (socio-cultural) perspectives. The method used is a literature study with a descriptive qualitative approach, analyzing primary and secondary sources such as tafsir, hadith, scientific literature, and relevant regulations. The findings reveal that the Qur'an and Hadith do not explicitly prohibit women's leadership, but rather emphasize principles of justice, meritocracy, and gender equality. The stories of female figures such as Queen Balqis, Khadijah, and Aisha prove the legitimacy of women's roles as leaders. However, the main challenges stem from patriarchal culture and narrow religious interpretations, which still limit women's roles in Islamic educational institutions. Women's leadership has proven to bring a more empathetic, inclusive, and effective managerial style in improving the quality of education. The implications of this study emphasize the importance of contextual reinterpretation of religious texts, strengthening gender equality regulations, and Islamic leadership training for women to create a fair and inclusive educational environment. Empowering women in Islamic educational leadership is the key to achieving a just and progressive society.